IMPLEMENTASI SISTEM PEMERIKSAAN DAN PERBAIKAN KERUSAKAN PADA DINDING BANGUNAN DI KELURAHAN NGADIRGO KECAMATAN MIJEN KOTA SEMARANG: IMPLEMENTASI SISTEM PEMERIKSAAN DAN PERBAIKAN KERUSAKAN PADA DINDING BANGUNAN DI KELURAHAN NGADIRGO KECAMATAN MIJEN KOTA SEMARANG - Kusumastuti, Dianita Ratna; Marsudi; Goro, Garup Lambang; Santosa, Stefanus; Supriyo; Rabinah, Aiun Hayatu; Praharseno, Fikri; Abdillah, Rifqi Aulia; Sulaiman, Sriwahyuningsih (Bangun Rekaprima, 2025)
Community service in the form of implementing a system for inspecting and repairing damage to building walls in Ngadirgo Village, Mijen District, Semarang City aims to increase the insight and skills of local residents regarding the problem of cracks in building walls that occur due to ground movement. This activity starts from a site survey, preparation of tools and materials, training on the correct procedures, ensuring the implementation of correct repair methods and according to standards. Based on the results of surveys and interviews with local residents, the cracks in the walls of RW 2 Hall, Ngadirgo Village, Mijen District were caused by ground movement activities, resulting in non-uniform settlement of the building structure. The service team and students provide training and assistance to residents and bricklayers in Ngadirgo Village, Mijen District. The repair method used to repair cracked walls is the stitching method